Production of amino acids from microalgae Nannochloropsis sp. biomass using subcritical water technology - Zainan, Nur Hidayah (2020)
The increase in the world population resulted in high demand for food, particularly proteins. Proteins are made up of long chains of amino acids. At present, animals and plants-based amino acids constitute the majority of the food that humans and livestock consume. However, due to the increase in demand, these amino acid resources will not be sufficient. Therefore, sources such as microalgae could be an alternative. Chemical synthesize and biological (enzyme and fermentation) methods are current methods to produce these amino acids. These methods used harmful chemicals, long processing steps, and high operating costs. Hence, finding a suitable amino acid production technique could significantly protect the environment, save time, and cost. This study deals with the use of the green technology approach, which is subcritical water technology. The yield and composition of amino acids produced from subcritical water of microalgae Nannochloropsis sp. were evaluated at different temperatures, time, and biomass loadings. The response surface methodology (RSM) was employed to generate empirical equations that correlate the subcritical water process parameters and the response variables, which are amino acids. The empirical equation generated was then evaluated to ensure the model adequately fit to describe and predict the production of amino acids. This study was also conducted to evaluate the kinetic and thermodynamic parameters of amino acid production from the microalgae using subcritical water technology. The results revealed the total and individual amino acids investigated produced the highest yield at different subcritical water conditions. Hence, careful selection of operating parameters (i.e., temperature, time, and biomass loading) is crucial to identify the selected amino acids when using subcritical water technology. The empirical equations obtained from RSM are inaccurate for predicting the yield of amino acids from the subcritical water of microalgae Nannochloropsis sp. biomass. However, the RSM study provides some ideas about the range of the optimum subcritical water conditions that might lead to a high yield of amino acid production. A high yield of total amino acids (1959 mg/100 g algae), leucine (134 mg/100 g algae), glycine (323 mg/100 g algae) and alanine (495 mg/100 g algae) was obtained in the kinetic study when using the optimum operating conditions, as suggested by the RSM approach. A single consecutive model used in the kinetic study is adequate to predict the production of the total amino acids, glycine, leucine and alanine at the studied temperature. The thermodynamic analysis results showed the subcritical water process as endothermic and constant energy supply needed to produce these amino acids. Overall, the findings from this study are useful to understand the production of the amino acid from microalgae Nannochloropsis sp. via the subcritical water process. Thus, the research will benefit food and pharmaceutical industries, where microalgae can be used as an alternative feedstock to meet the population's need for a more sustainable food supply, specifically concerning protein and amino acid demand.